157k views
8 votes
8n - 6(-5n - 3) = 18 + 7n step by step​

User Tete
by
4.8k points

2 Answers

7 votes

Answer: n= 0

Explanation:

Step 1: Simplify both sides of the equation.

8n−6(−5n−3)=18+7n

8n+(−6)(−5n)+(−6)(−3)=18+7n(Distribute)

8n+30n+18=18+7n

(8n+30n)+(18)=7n+18(Combine Like Terms)

38n+18=7n+18

38n+18=7n+18

Step 2: Subtract 7n from both sides.

38n+18−7n=7n+18−7n

31n+18=18

Step 3: Subtract 18 from both sides.

31n+18−18=18−18

31n=0

Step 4: Divide both sides by 31.

31n /31 = 0 /31

n=0

Answer:

n=0

User Rijo Simon
by
4.6k points
6 votes

Answer: n=0

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

8n−6(−5n−3)=18+7n

8n+(−6)(−5n)+(−6)(−3)=18+7n(Distribute)

8n+30n+18=18+7n

(8n+30n)+(18)=7n+18(Combine Like Terms)

38n+18=7n+18

Step 2: Subtract 7n from both sides.

38n+18−7n=7n+18−7n

31n+18=18

Step 3: Subtract 18 from both sides.

31n+18−18=18−18

31n=0

Step 4: Divide both sides by 31.

31n/31=0/31

n=0

User Monim
by
4.2k points